2018
DOI: 10.1038/s41598-018-31620-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel cell-based screening assay for small-molecule MYB inhibitors identifies podophyllotoxins teniposide and etoposide as inhibitors of MYB activity

Abstract: The transcription factor MYB plays key roles in hematopoietic cells and has been implicated the development of leukemia. MYB has therefore emerged as an attractive target for drug development. Recent work has suggested that targeting MYB by small-molecule inhibitors is feasible and that inhibition of MYB has potential as a therapeutic approach against acute myeloid leukemia. To facilitate the identification of small-molecule MYB inhibitors we have re-designed and improved a previously established cell-based sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…This concept was validated by studies of a mouse model of AML and by initial work on small-molecule compounds targeting MYB. These studies confirmed that MYB-inhibitory compounds can significantly prolong leukemia latency in mouse models of AML [ 10 , 12 19 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This concept was validated by studies of a mouse model of AML and by initial work on small-molecule compounds targeting MYB. These studies confirmed that MYB-inhibitory compounds can significantly prolong leukemia latency in mouse models of AML [ 10 , 12 19 ].…”
Section: Discussionsupporting
confidence: 56%
“…This has further stimulated interest in MYB as a target for drug development as such a drug would allow the elimination of the leukemia cells while sparing normal hematopoiesis [ 2 , 11 ]. Initial approaches based on small-molecule inhibitors of MYB have already yielded promising results, confirming that leukemia cells are more sensitive to targeting MYB than normal HPCs [ 12 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…All cell lines were originally obtained from ATCC and are free of mycoplasma contamination. HL60 cells expressing a C-terminally truncated MYB (MYB-CT3) and control HL60 cells were generated by lentiviral infection as described previously [ 43 , 45 ]. AML cells were grown in RPMI1640 medium supplemented with 10% FCS.…”
Section: Methodsmentioning
confidence: 99%
“…We have screened chemical compound libraries for low molecular weight MYB inhibitors, using a previously established MYB reporter cell line [ 42 , 43 , 44 ]. Here, we present the initial characterization of 2-amino-4-(3,4,5-trimethoxyphenyl)-4 H -naphtho[1,2- b ]pyran-3-carbonitrile (Bcr-TMP), a novel and highly active MYB-inhibitory compound.…”
Section: Introductionmentioning
confidence: 99%
“…Podophyllotoxin derivatives showed promising cytotoxicities against a set of human cancer cell lines HL-60 [267]. Teniposide and etoposide have been reported as inhibitors of MYB transcription factor [268]. GMZ-1 suppresses growth and induces apoptosis in adriamycinresistant K562/A02 cells through modulation of MDR1 expression [269].…”
Section: Podophyllotoxinsmentioning
confidence: 99%